The effect of additional neuromuscular electrical stimulation applied to erector spinae muscles on functional capacity, balance and mobility in post-stroke patients - Bilek, Furkan; Deniz, Gulnihal; Ercan, Zubeyde; Korkmaz, Nilufer Cetisli; Alkan, Gokhan (Ios Press, 2020)
OBJECTIVE: The aim of this study was to investigate the effects of neuromuscular electric stimulation applied to the erector spinae on balance, motor function and functional capacity in patients with stroke in a randomized controlled trial. METHODS: Sixty patients with stroke were recruited and randomly distributed into two groups: control group and neuromuscular electric stimulation group. All participants underwent conventional physical therapy five times a week for six weeks. The neuromuscular electric stimulation group received additional electrical stimulation. Outcome measures were evaluated with Brunnel Balance Assessment, Stroke Rehabilitation Movement Assessment, Functional Ambulation Classification, Adapted Patient Evaluation and Conference System, Postural Assesment Scale for Stroke patients, Short Form-36, and Minimental State Examination scales. RESULTS: Significant differences were observed in all scores at the end of the study in both groups. Postural Assesment Scale for Stroke patients and Stroke Rehabilitation Movement Assessment scores were higher in the neuromuscular electric stimulation group compared to the control group (p < 0.05). All the other scores were not statistically significant. CONCLUSION: It is recommended to evaluate and treat trunk muscle, which is usually neglected in treatment, and to consider the combination of conventional treatment and neuromuscular electric stimulation when designing an ideal rehabilitation program.
Keywords: Neuromuscular electrical stimulation; erector spinae; stroke; functional capacity; balance; mobility